nalysis of patient service time in the department of pediatric dentistry of Baiturrahmah dental and oral education hospital: Study cross-sectional - Oktaviani, Oktaviani; Surya, Leny Sang (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
ABSTRACTIntroduction: Dental and Oral Teaching Hospitals have a dual role as healthcare providers and educational institutions, requiring efficient and high-quality services. Service time is a key indicator of service quality, particularly in pediatric dental care, which involves unique psychological and behavioral characteristics. This study aims to analyze pediatric patient service time and identify factors influencing its duration at the Department of Pediatric Dentistry, RSGMP Baiturrahmah Padang. Methods: This study employed a mixed-method design. The quantitative component used a cross-sectional approach with total sampling of 100 pediatric patients, and the data were analyzed descriptively using the variables man, method, material, machine, and money. The qualitative component was conducted through in-depth interviews with 6 key informants selected using purposive sampling, focusing on the duration of service time, and with data analyzed using thematic analysis. Results: The average service time was 96.09 minutes per patient, with most services conducted within the 60–120 minutes range. Factors influencing service duration included human resources, methods and workflow, facilities and infrastructure, medical equipment condition, and patient related-factors, particularly children’s behavior. Conclusion: Pediatric dental service time has not yet achieved optimal efficiency. Improvements in service systems, the establishment of standardized service time benchmarks, and enhanced faciity and human resource readiness are needed to improve service efficiency and quality.KEYWORDS: service time, pediatric dentistry, service quality, service efficiencyAnalisis waktu pelayanan pasien di departemen kedokteran gigi anak rumah sakit gigi dan mulut pendidikan: Studi cross-sectionalABSTRAKPendahuluan: Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP) memiliki peran ganda sebagai institusi pelayanan dan pendidikan, sehingga dituntut memberikan pelayanan yang bermutu dan efisien. Waktu pelayanan merupakan indikator penting mutu pelayanan, khususnya pada kedokteran gigi anak yang memiliki karakteristik psikologis dan perilaku khusus. Tujuan penelitian ini bertujuan menganalisis waktu pelayanan pasien anak dan mengidentifikasi faktor-faktor yang memengaruhi lamanya waktu pelayanan di Departemen Kedokteran Gigi Anak (KGA) Rumah Sakit Gigi dan Mulut Pendidikan (RSGMP). Metode: Penelitian ini menggunakan desain mix method. Pendekatan kuantitatif menggunakan desain cross-sectional dengan total sampling terhadap 100 pasien anak, dianalisis secara deskriptif dengan variabel man, method, material, machine, money. Pendekatan kualitatif dilakukan melalui wawancara mendalam terhadap 6 informan kunci yang dipilih secara purposive sampling, dengan variabel lama waktu pelayanan, serta dengan analisis tematik. Hasil: Rerata waktu pelayanan pasien anak adalah 96,09 menit per pasien, dengan mayoritas berada pada rentang 60–120 menit. Faktor yang memengaruhi waktu pelayanan meliputi sumber daya manusia, metode dan alur kerja, ketersediaan sarana dan prasarana, kondisi peralatan medis, serta karakteristik pasien anak. Simpulan: Waktu pelayanan di Departemen KGA RSGMP Baiturrahmah Padang belum sepenuhnya efisien. Diperlukan perbaikan sistem pelayanan, penetapan standar waktu pelayanan, serta peningkatan sarana dan kesiapan sumber daya manusia.KATA KUNCI: waktu pelayanan, kedokteran gigi anak, mutu pelayanan, efisiensi pelayanan.